Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the value of [tex]\( y \)[/tex] for the point [tex]\( P\left(-\frac{3}{5}, y\right) \)[/tex] that lies on the unit circle in the second quadrant, we start with the equation of a unit circle:
[tex]\[ x^2 + y^2 = 1 \][/tex]
Given [tex]\( x = -\frac{3}{5} \)[/tex], substitute this value into the equation:
[tex]\[ \left(-\frac{3}{5}\right)^2 + y^2 = 1 \][/tex]
Now, calculate [tex]\( \left(-\frac{3}{5}\right)^2 \)[/tex]:
[tex]\[ \left(-\frac{3}{5}\right)^2 = \frac{9}{25} \][/tex]
Next, substitute [tex]\( \frac{9}{25} \)[/tex] in place of [tex]\( \left(-\frac{3}{5}\right)^2 \)[/tex]:
[tex]\[ \frac{9}{25} + y^2 = 1 \][/tex]
To solve for [tex]\( y^2 \)[/tex], subtract [tex]\( \frac{9}{25} \)[/tex] from both sides of the equation:
[tex]\[ y^2 = 1 - \frac{9}{25} \][/tex]
Convert 1 into a fraction with the same denominator:
[tex]\[ 1 = \frac{25}{25} \][/tex]
Now perform the subtraction:
[tex]\[ y^2 = \frac{25}{25} - \frac{9}{25} = \frac{16}{25} \][/tex]
Thus,
[tex]\[ y^2 = \frac{16}{25} \][/tex]
To find [tex]\( y \)[/tex], take the square root of both sides:
[tex]\[ y = \sqrt{\frac{16}{25}} \][/tex]
Since [tex]\( y \)[/tex] is in the second quadrant, where [tex]\( y \)[/tex] values are positive:
[tex]\[ y = \frac{\sqrt{16}}{\sqrt{25}} = \frac{4}{5} \][/tex]
Therefore, the value of [tex]\( y \)[/tex] is:
[tex]\[ y = \frac{4}{5} \][/tex]
Thus, [tex]\( y = 0.8 \)[/tex]
[tex]\[ x^2 + y^2 = 1 \][/tex]
Given [tex]\( x = -\frac{3}{5} \)[/tex], substitute this value into the equation:
[tex]\[ \left(-\frac{3}{5}\right)^2 + y^2 = 1 \][/tex]
Now, calculate [tex]\( \left(-\frac{3}{5}\right)^2 \)[/tex]:
[tex]\[ \left(-\frac{3}{5}\right)^2 = \frac{9}{25} \][/tex]
Next, substitute [tex]\( \frac{9}{25} \)[/tex] in place of [tex]\( \left(-\frac{3}{5}\right)^2 \)[/tex]:
[tex]\[ \frac{9}{25} + y^2 = 1 \][/tex]
To solve for [tex]\( y^2 \)[/tex], subtract [tex]\( \frac{9}{25} \)[/tex] from both sides of the equation:
[tex]\[ y^2 = 1 - \frac{9}{25} \][/tex]
Convert 1 into a fraction with the same denominator:
[tex]\[ 1 = \frac{25}{25} \][/tex]
Now perform the subtraction:
[tex]\[ y^2 = \frac{25}{25} - \frac{9}{25} = \frac{16}{25} \][/tex]
Thus,
[tex]\[ y^2 = \frac{16}{25} \][/tex]
To find [tex]\( y \)[/tex], take the square root of both sides:
[tex]\[ y = \sqrt{\frac{16}{25}} \][/tex]
Since [tex]\( y \)[/tex] is in the second quadrant, where [tex]\( y \)[/tex] values are positive:
[tex]\[ y = \frac{\sqrt{16}}{\sqrt{25}} = \frac{4}{5} \][/tex]
Therefore, the value of [tex]\( y \)[/tex] is:
[tex]\[ y = \frac{4}{5} \][/tex]
Thus, [tex]\( y = 0.8 \)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.